Stockhausen in den Höhlen von Jeita: Colour film by Luc Ferrari 1969 - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 2010)
Luc Ferrari made this film in November 1969 for the French film society MIDEM. ( Also inthe film: Max Ernst, André Masson and other artists. ) The following Stockhausen works wereperformed: November 22nd 1969: SPIRAL ( Globokar ) - SPIRAL (Vetter) - INTENSITÄT( INTENSITY ) - SETZ DIE SEGEL ZUR SONNE ( SET SAIL FOR THE SUN ); November23rd: TELEMUSIK - STIMMUNG; November 24th: SPIRAL ( Bojé ) - KURZWELLEN;November 25th: HYMNEN ( Alings, Bojé, Gelhaar, Fritsch, Eötvös ).